The ancient CYP716 family is a major contributor to the diversification of eudicot triterpenoid biosynthesis - Karel Miettinen (Nature Portfolio, 2017)
Cytochrome P450 family enzymes have an essential role in the creation of triterpenoid diversity in plants. Here, the authors describe triterpenoid synthesis as mediated by CYP716 enzymes in medicinal plant species, and perform phylogenetic analysis to describe CYP716 molecular evolution in plants.